Pengaruh Financial Literacy dan Risk Perception terhadap Keputusan Investasi Generasi Millennial Kota Padang - Yola Yolanda; Abel Tasman (Universitas Negeri Padang, 2020)
This study aims to look at the influence of Financial Literacy and the effect of Risk Perception on the investment decisions of millennial generation of Padang City. The type of this research is a comparative causal research (causative). The samplesof this study was 96 respondents ofmillennial generation of Padang City that choosed by using purposive sampling method. The types of data in this study are primary data and secondary data. The data was collected by questionnairy technique and it was analysed byusing multiple regression analysis method. The instrument testing uses validity and reliability tests. The analysis prerequisite tests conducted include normality test, heterokedasticity test and multicollinearity test. The data collected was processed with SPSS version 20.0. The results of this study indicate that both of Financial Literacy and Risk Perception has a significant positive effect on investment decisions of millennial generation of Padang City. Keywords : financial literacy, risk perception